2011
DOI: 10.1186/1471-2164-12-523
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Streptococcus suis reveals significant genomic diversity among different serotypes

Abstract: BackgroundStreptococcus suis (S. suis) is a major swine pathogen and an emerging zoonotic agent. Serotypes 1, 2, 3, 7, 9, 14 and 1/2 are the most prevalent serotypes of this pathogen. However, almost all studies were carried out on serotype 2 strains. Therefore, characterization of genomic features of other serotypes will be required to better understand their virulence potential and phylogenetic relationships among different serotypes.ResultsFour Chinese S. suis strains belonging to serotypes 1, 7, 9 and 1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 56 publications
9
61
0
1
Order By: Relevance
“…Yet, SuiR alone was able to activate P suiA transcription, though at low efficiency, as was also observed with BovR and SpaR (24,48). Interestingly, the genome of an S. suis serotype 9 strain isolated in China was recently sequenced and shown to contain an intact sui locus (SSUD12_1302-SSUD12_1310) nearly identical to the one unveiled here (40). Although it has not been tested for lantibiotic production, the operonic association of suiK-suiR with the intact sui locus might underscore its connection to suicin production.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Yet, SuiR alone was able to activate P suiA transcription, though at low efficiency, as was also observed with BovR and SpaR (24,48). Interestingly, the genome of an S. suis serotype 9 strain isolated in China was recently sequenced and shown to contain an intact sui locus (SSUD12_1302-SSUD12_1310) nearly identical to the one unveiled here (40). Although it has not been tested for lantibiotic production, the operonic association of suiK-suiR with the intact sui locus might underscore its connection to suicin production.…”
Section: Discussionsupporting
confidence: 70%
“…Following the clue of SuiK-SuiR sharing similarity with the TCS for lantibiotic regulation and comparison of its neighboring lan relics with bovicin HJ50 and salivaricin gene clusters, a primarily identical but disrupted sui locus was unveiled and reannotated in three SS2 genomes. Indeed, sui locus was potentially wide distributed in Chinese S. suis isolates because of its location on the 89K PAI (39,40). Notably, similar situations were also observed in cytolysin determinants in E. faecalis and the sal locus in S. pyogenes such that intact or disrupted versions were unveiled in different strains (31,41,42).…”
Section: Discussionmentioning
confidence: 84%
“…We selected 72 isolates from 117 isolates that were previously typed using MLST. Together with 13 available completed genomes (11,12,15,(16)(17)(18), a total of 85 strains were used for this study. These 85 isolates included all 32 serotypes of reference strains.…”
Section: Methodsmentioning
confidence: 99%
“…As described above and shown in Table 1, all Wzy polymerases, except for those of serotypes 1 and 14 (HG50) and serotypes 2 and 1/2 (HG54), were allocated to serotype-specific HGs. The cps gene clusters of serotypes 1 and 14 and those of serotypes 2 and 1/2 were shown to be almost identical in each pair (17,24), suggesting that the repeat unit structures of CPs are also very similar in each pair. Therefore, Wzy polymerases may differ from each other according to the repeat unit structures in the respective serotypes.…”
Section: Assignment Of Hgsmentioning
confidence: 95%
“…In serotypes 6,11,12,13,15,17,18,20,21,22,24,27,28,29,30, and 31, partial sequences of the cps gene clusters (orfY-cpsD genes) have been determined and deposited in the GenBank database (accession numbers JF791152 to JF791167). Furthermore, complete genome sequences of 13 S. suis nonreference strains (seven of serotype 2 and one of serotypes 1, 1/2, 3, 7, 9, and 14) have been determined to date (19)(20)(21)(22)(23)(24). A previous study analyzing 15 S. suis cps gene clusters indicated that all the cps gene clusters are located between the orfZ (conserved hypothetical protein gene) and aroA (3-phosphoshikimate 1-carboxyvinyltransferase gene) genes on the chromosome.…”
mentioning
confidence: 99%